Error analysis of exterior orientation elements on geolocation for a Moon-based Earth observation optical sensor. Issue 3 (3rd March 2020) - Guo, Huadong; Ye, Hanlin; Liu, Guang; Dou, Changyong; Huang, Jing
ABSTRACT: The Moon is a potential new platform for Earth observation. The advantages of its large-scale observational scope, long temporal duration, and multi-layer detecting of the Earth will undoubtedly advance our understanding of the Earth system. To carry out the observations from a Moon-based optical sensor, the geolocation error caused by exterior orientation elements need to be investigated. This paper analyses the error effects of exterior orientation elements on geolocation for an optical sensor. To estimate the error, we present a geometric image model and utilise some parameters to measure the image offsets. Through a large number of numerical simulations, the results demonstrate that the image offsets are not obvious influenced by the distance and observation angle at mid-high latitude of the Moon and have linear correlation with the increasing errors of the exterior orientation elements. Further, the relationship between the spatial resolution and errors of exterior orientation elements are revealed. Finally, the error characteristics for Moon-based Earth observation are discussed. It is expected that the conclusion drawn in this paper could support the study of a Moon-based Earth observation optical sensor.